A Reflection on Gender Role Inequality in Domestic Relations Through Paris Paloma’s Song ‘Labour’: A Fiqh Al-Usrah Perspective - Hasanah Harahap, Nurizka (Journal Research of Social Science, Economics, and Management, 2025)
Labor Paris Paloma’s work speaks volumes anger Woman to inequality role domestic which becomes reflection real How mark equality the often ignored in life everyday . Through sharp metaphors and lyrics , the song This reflect burden double , manipulation emotional and relationship unequal power in realm public and domestic . This article use approach qualitative descriptive For analyze representation gender inequality in lyrics song labor . Through perspective Fiqh al- Usrah , results analysis show that values patriarchal criticism in song the contradictory with Islamic principles about relation a fair , equal and full family love . In Islam, men and women created from the same element ( nafs ) Wahidah ) and has position equal before Allah SWT . Principle morals justice , deliberation , and relations partnership must mainstreamed in distribution role domestic . With Thus , Fiqh al- Usrah give framework ethics at a time law For overcome practice gender inequality in modern family . This study confirm that work culture popular like song can become a reflective medium at a time criticism social to practice religion and culture that have not been fully in favor of gender justice.